Hegel’s presence in Rorty - Kwiek, Marek (My University, 1996)
Hegel is a philosophical giant that appears in all Rorty’s books, his specter hovers over the Rortyan conception of philosophy and his attitude towards the history of philosophy. But Rorty is interested only in one side of Hegel’s philosophy, namely the Hegel from Phenomenology of Spirit rather than the older Hegel - the creator of the system. The "young Hegel" is one of the greatest Rorty’s heroes (if we think of his philosophical figures in term of good and bad guys, heroes and villains). Rorty never devoted an article to him, nor did he write about him more than a page or two in one place. He never wrote about him in the way a historian of philosophy writes about his "subject" - in a detailed, strict, severe and dull manner. In a great narrative about the history of philosophy written over the years by Rorty, Hegel appears as a turning point in European philosophical tradition: it is he who breaks the "Plato-Kant canon”, who begins the "tradition of ironist philosophy", as Rorty labels it, continued by Nietzsche, Heidegger and Derrida. He is the founder of such kind of philosophy - called also by Rorty a "literary genre" or (cultural) "criticism" - in which philosophers define their achievements through the relation with their predecessors rather than with truth. He is for Rorty a paradigm of the ironist’s abilities to use the possibilities offered by redescriptions of the past. And finally it is he who in Rorty’s stories is opposed to Kant (and Plato) - in the history of philosophy Rorty always favors "Hegelians" as opposed to "Kantians" in his specific sense of both terms. He is for Rorty a paradigm of historicism, a model way in which one can abandon the ideal of philosophy as a search for ahistorical, atemporal and transcendental truths. Historicization of reason, "temporalization of rationality" - was "the single most important step in arriving at the pragmatist’s distrust of Philosophy", Rorty says about Hegel in his "Introduction" to Consequences of Pragmatism Hegel gave philosophy the sense of finitude, temporality, historicity of its problems, helped it to realize that vocabularies change in history, that they are temporal and transient. Rorty’s Hegel is a romantic conducting congenial reinterpretations of earlier interpretations, presenting redescriptions of redescriptions, telling stories about old stories in a new terminology; Hegel is a "poet" in Rorty’s wide sense of the term (that is, "one who makes things new”), a "strong philosopher" who is interested in dissolving old, inherited problems rather than in solving them.
Keywords: Richard Rorty; neopragmatism; new pragmatism; American pragmatism; Hegel; Hegelianism; Phenomenology of Spirit; redescription; Phenomenology of mind; liberal ironist; Contingency, Irony, and Solidarity; What is Pragmatism; Consequences of Pragmatism; Philosophy and the Mirror of Nature; literary criticism; postmodernism; strong misreading; American philosophy; German philosophy; recontextualization; storytelling; history of philosophy